Ecological and Sustainability Assessment of Mangrove Ecosystem in Gili Sulat and Gili Lawang, East Lombok, Indonesia - Putri, Andini Suciningtyas; Khusaini, Mohammad; Adiyoso, Wignyo (Media Konservasi, 2025)
Small islands in Indonesia hold significant potential for tourism development and biodiversity conservation. However, their sustainability is increasingly threatened by various vulnerabilities. The Gili Sulat and Gili Lawang possess significant ecological, economic, and social potential through the presence of mangrove ecosystems. A balanced approach to managing sustainability across multiple dimensions is therefore essential to preserve protected forests. The gap between mangrove management on small islands and larger islands, in terms of area coverage, community dependence, utilization conflicts, and management strategies, highlights the significance of this study. This research aimed to measure the level of mangrove sustainability from multi-dimensional perspectives using the Rapid Appraisal (RAPFISH) method combined with a remote sensing approach. The RAPFISH analysis resulted in an overall sustainability index of 52.79%, indicating a moderately sustainable status. While the key ecological functions of the mangrove ecosystems remain preserved, further efforts are necessary in areas such as local economic development and institutional capacity to achieve a fully sustainable condition. Leverage analysis identified nine sensitive attributes out of 30 that significantly influence sustainability outcomes and guide future strategies. The Forest Canopy Density (FCD) model shows that coastal mangrove areas maintain high canopy density. Intensified patrols, conservation-based educational ecotourism, mangrove-based livelihoods, ecosystem management plans, and strengthened institutional collaboration are among the strategies to enhance sustainability. The study implies that mangrove sustainability depends on targeted adaptive management of the most influential attributes.